Strong ground motion from the seismic swarms preceding the 2021 and 2022 volcanic eruptions at Fagradalsfjall, Iceland - Hernandez-Aguirre V. M.; Rupakhety R.; Olafsson S.; Bessason B.; Erlingsson S.; Paolucci R.; Smerzini C. (Bulletin of Earthquake Engineering, 2023)
The Geldingadalir and Meradalir eruptions at Mt. Fagradalsfjall in the Reykjanes Peninsula on 19 March 2021 and 3 August 2022, respectively, were preceded by intense volcano-tectonic swarms. Eight earthquakes with M ≥ 5 were recorded by the Icelandic Strong Motion Network. We present an overview of the seismicity in Fagradalsfjall, and salient features of the strong ground motion caused by the swarms in the epicentral area. The largest recorded horizontal Peak Ground Acceleration (PGA) was ~ 0.45 g at Grindavík, which is the strongest PGA recorded in Iceland since the MW6.3 2008 Ölfus Earthquake. Recorded waveforms show a rich long-period energy content, with a burst of higher frequencies at the beginning of shaking. This leads to larger response spectral accelerations at long periods that those from typical shallow crustal earthquakes. Moreover, an empirical mixed-effects ground motion model for PGA, PGV and PSA was calibrated for rock sites based on the available recordings. The attenuation rate from this model is similar to that introduced by Lanzano and Luzi (Bull Earthq Eng 18(1):57–76, 2020) which is based on data from volcanic events in Italy, but the magnitude scaling of our model is much lower. The overall results indicate that scaling and attenuation of ground motion from volcanic events and purely tectonic earthquakes in Iceland are different. This is an important observation because seismic hazard in parts of the Reykjavik area and of the central highlands, where important hydroelectric power plants are located, could potentially be dominated by events of volcanic origin. Therefore, it is important to take these observations into account for seismic hazard and risk assessment in Iceland.